perubahan fungsi sepeda listrik dari alat transportasi menjadi sarana mata pencarian di kota solok - Rossanda Isin Bayeva; Maulid Hariri Gani; Nisbatun Nisak (STKIP Subang, 2026)
This study discusses the transformation of electric bicycles from transportation tools into means of livelihood in Solok City. This phenomenon can be seen through the use of electric bicycles by mobile culinary vendors such as coffee sellers, ampera food sellers, and fried chicken vendors. This research used a qualitative method with a descriptive approach through observation, interviews, and documentation. The study applies the concept of technology appropriation by Roger Silverstone and Eric Hirsch within the framework of Science and Technology Studies (STS). The results show that electric bicycles have transformed into mobile trading tools that support community economic activities because they are more practical, flexible, and cost-efficient. This phenomenon reflects a process of technology appropriation, where technology is reinterpreted according to the social and economic needs of society.